Les usages de la route dans le Mexique colonial : histoires de vie et mobilités du XVIe au XIXe siècle - Raffaele Moro-Romero (Nuevo mundo - Mundos Nuevos, 2007)
Through the comment of about twenty life stories and reconstruction of an itinerant religious practice (alms collection), this thesis is about mobility in Colonial Mexico (New Spain). New knowledges regarding neohispanic mobility have allowed mexicanist historiography updating the main lines of the topic, giving us the opportunity to concentrate on the dimension of true-life and individual practices. The selection of a microscopic scale and a biographical approach has allowed identifying a certain number of behaviours proper to a true culture of mobility. The study points out those inhabitants of Colonial Mexico have often been characterized by an alternation of periods of mobility and periods of sedentary lifestyle. This mobility has been one of the resources used by people to face constraints particular to the Hispanic-american society in the colonial times.